SOMIB news - ., Sociedad Mexicana de Ingeneiria Biomedic (Revista Mexicana de Ingenieria Biomedica, 2018)
This new section that we make available to you is responsible for the selection of products related to Biomedical Engineering. We hope the collaboration of the partners sending reports or news of interest.